How Video Rental Patterns Change as Consumers Move Online - Zentner, Alejandro; Smith, Michael; Kaya, Cuneyd (Management Science, 2013)
How will consumption patterns for popular and “long-tail” products change when consumers move from brick-and-mortar to Internet markets? We address this question using customer-level panel data obtained from a national video rental chain as it was closing many of its local stores. These data allow us to use the closure of a consumer's local video store as an instrument, breaking the inherent endogeneity between channel choice and product choice. Our results suggest that when consumers move from brick-and-mortar to online channels, they are significantly more likely to rent “niche” titles relative to “blockbusters.” This suggests that a significant amount of niche product consumption online is due to the direct influence of the channel on consumer behavior, not just due to selection effects from the types of consumers who decide to use the Internet channel or the types of products that consumers decide to purchase online. This paper was accepted by Pradeep Chintagunta, marketing.